PENGARUH PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT III TERHADAP MOTIVASI KERJA, KARIER DAN KOMPETENSI PEGAWAI PEMERINTAH PROVINSI JAWA TIMUR - Moeheriono Moeheriono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
Since the legislation No. 22.1999 started in autonomy region era and operates three until four years lately by giving large. Authority for all regions to utilize the potency or region revenue to support human resources development for it's region development. One of big problems for almost all regions in this autonomy era lately is about quality and quantity which less and scarce on human resources in a region. Concerning those problem, the development of human resources become crucial object to be described in this research.The objectives of the research reported in this dissertation are to examine and explain the effect of Leadership Training Course Level III (DIKLATPIM TINGKAT III) in Provincial  Government of East Java. More specifically, the research attemts to explain the causal relationship (direct and indirect) between the variables involved, by taking into account employee work motivation, career, and competency.The data was gathered through the administration of questionnaires as well as direct interview with a selected subjects. One hundred and seventy eight individuals were chosen from all former attendants of the Leadership Training Course Level III (DIKLATPIM TINGKAT III) in East Java Province using a random sampling procedure. Then, a structural equation modeling (SEM) technique was employed to analyze the data.The results of the research discover that Leadership Training Course Level III (DIKLATPIM TINGKAT III) has a significant positive effect on employee work motivation and competency. Moreover, it is also found that Leadership Training Course Level III (DIKLATPIM TINGKAT III) does not have a direct effect on employee career. Other additional findings are also reported and further discussed, while several recommendations for future research are developed.